PENGGUNAAN MEDIA POWER POINT BERBASIS HYPERLINK UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS VSD INPRES 3/77 WATU KECAMATAN BAREBBO KABUPATEN BONE - Muliadi, Muliadi; Mujahidah, Mujahidah; Nurhalizah, Siti (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study is a classroom action research aimed at determining whether the use of Hyperlink-Based PowerPoint media can improve the learning outcomes of IPAS subject for fifth-grade students at SD Inpres 3/77 Watu, Barebbo District, Bone Regency. The subjects of this study were all 17 fifth-grade students and the homeroom teacher. Data collection techniques included observation and tests. The data analysis techniques used in this study were data reduction, data description, and conclusion drawing.Based on the research findings, students' learning outcomes improved through the use of Hyperlink-Based PowerPoint media. This is evident from the percentage of learning outcomes in Cycle I, which reached the